Benefits and Challenges of Telework During The Covid-19 Pandemic - Saragih, Susanti; Setiawan, Santy; Markus, Teddy; Rhian, Peter (International Research Journal of Business Studies, 2021)
During the Covid-19 pandemic, the term work from home (WFH) has been introduced to refer to a work arrangement in which individual can complete their duties while they are at home. While most flexible work arrangements are a preference, work from home is mandatory. Therefore, the impact of WFH during the Covid-19 pandemic needs to be studied. The total respondent of this study is 337 employees, who are works at home during the pandemic. The results showed that the three main benefits employees might gain during WFH are flexibility, more time with family, and less travel time. On the other side, employees struggle to balance their personal and work life, access to websites or software, and limited devices and workspace. Most of the companies are not ready for the WFH scheme though some of them gave support to employees (e.g., quota subsidy). This research gave some essential suggestions for HR managers in designing remote work for the future.